Deinococcus enclensis sp nov., isolated from a marine sediment sample - Thorat, Meghana N.; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Ramana, V. Venkata; Joseph, Neeta; Shouche, Yogesh S.; Dastager, Syed Gulam (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A novel pale-pink coloured strain, designated NIO-1023(T), was isolated from a marine sediment sample from Chorao Island, Goa, India. The taxonomic position of strain NIO-1023(T) was investigated by using a polyphasic approach. The cells were observed to be Gram-stain positive, coccal shaped and non-spore forming. Phylogenetic analyses using the 16S rRNA gene sequence of the isolate indicated that the organism belongs to the genus Deinococcus. The strain NIO-1023(T) showed highest 16S rRNA gene sequence similarities with Deinococcus ficus (97.8 %), whereas other Deinococcus species showed less than 95 % sequence similarity. The DNA-DNA relatedness with respect to D. ficus CC-FR2-10(T) was 23.9 %. Chemotaxonomic data revealed that strain NIO-1023(T) contains only menaquinone MK-8 as the respiratory quinone and a complex polar lipid profile consisting of different unidentified glycolipids and polar lipids, two unknown phospholipids and three unknown phosphoglycolipids. As in other deinococci, one of these phosphoglycolipids was predominant in the profile. The predominant fatty acids were identified as C-17:1 w8c, C-16:1 w6c/w7c, C-15:1 w6c and C-17:1 w9c. The genomic DNA G + C content of strain NIO-1023(T) was determined to be 67.2 mol%. The biochemical and chemotaxonomic properties demonstrate that strain NIO-1023(T) represents a novel species, for which the name Deinococcus enclensis sp. nov. is proposed. The type strain is NIO-1023(T) (=DSM 25127(T) = NCIM 5456(T)).
Keywords: 16S rRNA; Deinococcus; Marine sediments; Polyphasic

Description of Lysinibacillus telephonicus sp nov., isolated from the screen of a cellular phone - Rahi, Praveen; Kurli, Rashmi; Khairnar, Mitesh; Jagtap, Shubhangi; Pansare, Aabeejjeet N.; Dastager, Syed G.; Shouche, Yogesh S. (International Journal of Systematic and Evolutionary Microbiology, 2017)
A novel bacterial strain, designate dS5H2222(T), was isolated form the screen of a cellular phone. The cells were Gram-stainpositive, rod-shaped, aerobic and motile, and endospores are formed. S5H2222(T) grew as pale white colonies on trypticase soy agar and the best growth was observed at 37 degrees C (10- 55 degrees C) and at pH 7.0 (5.0-9.0). S5H2222(T) could tolerate up to 10% (w/v) NaCl. Phylogenetic analysis based on 16S rRNA gene sequences placed this strain within the genus Lysinibacillus and it exhibited high 16S rRNA gene sequence similarity to Lysinibacillus halotolerans LAM612(T) (97.8 %), Lysinibacillus chungkukjangi2RL3-2(T) (97.4 %) and Lysinibacillus sinduriensis BLB-1(T) (97.2 %). TheDNA- DNA relatedness of the strain with L. halotolerans JCM 19611(T), L. chungkukjangi KACC 16626(T) and L. sinduriensis KACC 16611(T) was 57, 64 and 55% respectively. The genomic DNA G+C content was 39.8 mol%. The major fatty acids of S5H2222(T) were iso-C-15:0, anteiso-C-15:0, iso-C-16:0 and anteiso-C-17:0. MK-7 was the only menaquinone and the main polar lipids were diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine, four unidentified polar lipids were also present. The diagnostic amino acids in the cell wall peptidoglycan contained Lys-Asp (type A4 alpha). On the basis of the results of the phenotypic and genotypic characterizations, it was concluded that S5H2222(T) represents a novel species of the genus Lysinibacillus, for which the name Lysinibacillus telephonicus sp. nov. is proposed. The type strain is S5H2222(T) (=MCC 3065 T =KACC 18714(T)=LMG 29294(T)).

Draft genome sequence of lactobacillus plantarum strains E2C2 and E2C5 isolated from human stool culture - Suryavanshi, Mangesh V.; Paul, Dhiraj; Doijad, Swapnil P.; Bhute, Shrikant S.; Hingamire, Tejashri B.; Gune, Rahul P.; Shouche, Yogesh S. (Standards in Genomic Sciences, 2017)
Probiotic Lactobacillus species offer various health benefits, thus have been employed in treatment and prevention of various diseases. Due to the differences in the isolation source and the site of action, most of the lactobacilli tested in-vitro for probiotics properties fail to extend similar effects in-vivo. Consequently, the search of autochthonous, efficacious and probably population specific probiotics is a high priority in the probiotics research. In this regards, whole genome sequencing of as many Lactobacillus as possible will help to deepen our understanding of biology and their health effects. Here, we provide the genomic insights of two coherent oxalic acid tolerant Lactobacillus species (E2C2 and E2C5) isolated from two different healthy human gut flora. These two isolates were found to have higher tolerance towards oxalic acid (300 mM sodium oxalate). The draft genome of strain E2C2 consists of 3,603,563 bp with 3289 protein-coding genes, 94 RNA genes, and 43.99% GC content, while E2C5 contained 3,615,168 bp, 3293 coding genes (93.4% of the total genes), 95 RNA genes and 43.97% GC content. Based on 16S rRNA gene sequence analysis followed by in silico DNA-DNA hybridization studies, both the strains were identified as Lactobacillus plantarum belonging to family Lactobacillaceae within the phylum Firmicutes. Both the strains were genomically identical, sharing 99.99% CDS that showed 112 SNPs. Both the strains also exhibited deconjugation activity for the bile salts while genome analysis revealed that the L. plantarum strains E2C2 and E2C5 also have the ability to produce vitamins, biotin, alpha-and beta-glucosidase suggesting potential probiotic activities of the isolates. The description presented here is based on the draft genomes of strains E2C2 and E2C5 which are submitted to GenBank under the accession numbers LSST00000000.1 and LTCD00000000.1, respectively.